PENGARUH SELF EFFICACY, PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI JAWA TIMUR - Tio Alvino Halim; Ida Aju Brahmasari (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
Knowing how self efficacy, training, and work environment affect the performance of employees of the East Java Provincial Marine and Fisheries Service is the purpose of this study. With a sample size of 65 people, the research population is the effect of employee performance of the East Java Provincial Maritime and Fisheries Service. A quantitative approach was used in this study, and IBM SPSS Statistics Version 30 was used for data testing. To analyse the hypotheses, several analytical techniques such as multiple linear regression, F-test, and T-test were used. In addition, testing of data instruments, including validity and reliability assessments and traditional assumption tests such as heteroscedasticity, multicollinearity, and normality tests, were conducted to ensure data reliability. The results of this study show the influence of self efficacy, training, and work environment, on the influence of employee performance. It has been proved that self efficacy, training, and work environment, all influence competence and self ability on employee performance significantly and positively. These results prove that the three variables have a significant role in influencing the ability on employee performance of the East Java Provincial Marine and Fisheries Service.